1990
DOI: 10.1021/bi00489a017
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and mutagenesis of the catalytic domain of dihydrolipoamide acetyltransferase from Saccharomyces cerevisiae

Abstract: The inner core domain (residues approximately 221-454) of the dihydrolipoamide acetyltransferase component (E2P) of the pyruvate dehydrogenase complex from Saccharomyces cerevisiae has been overexpressed in Escherichia coli strain JM105 via the expression vector pKK233-2. The truncated E2p was purified to apparent homogeneity. It exhibited catalytic activity (acetyl transfer from [1-14C]acetyl-CoA to dihydrolipoamide) very similar to that of wild-type E2p. The appearance of the truncated and wild-type E2p was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
5
29
0
Order By: Relevance
“…This suggests that the conserved active‐site histidine is not absolutely required for substrate hydrolysis; we did not assess ester production by H191A, and it may be that the alcohol acyltransferase reaction is abolished in this mutant. The H191A mutation leaves K M essentially unchanged, and this was anticipated since results with other acyltransferases suggest that the catalytic histidine can play only a minor role in determining substrate binding affinity (Lewendon et al, ; Suzuki et al, ; Niu et al, ; Hsiao et al, ). The exception to this general trend is at C14 chain lengths, where the K M of H191A is ~20 times larger than that of wild‐type protein.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that the conserved active‐site histidine is not absolutely required for substrate hydrolysis; we did not assess ester production by H191A, and it may be that the alcohol acyltransferase reaction is abolished in this mutant. The H191A mutation leaves K M essentially unchanged, and this was anticipated since results with other acyltransferases suggest that the catalytic histidine can play only a minor role in determining substrate binding affinity (Lewendon et al, ; Suzuki et al, ; Niu et al, ; Hsiao et al, ). The exception to this general trend is at C14 chain lengths, where the K M of H191A is ~20 times larger than that of wild‐type protein.…”
Section: Discussionmentioning
confidence: 96%
“…In both enzymes (Fig. This interpretation is supported by the mutagenesis studies on the E. coli enzyme (27) but not by those on the yeast molecule (28), where the replacement of this His by Ala does not affect the activity. Such a conformation allows a hydrogen bond between the imidazole nitrogen NM1 and the carbonyl 0 of the same amino acid.…”
Section: Parametermentioning
confidence: 90%
“…Direct Demonstration of Acetyl Transfer between E2p DomainsIt had been reported that E2p and independently expressed E2pCD catalyze the model reaction using acetyl-CoA as acetyl donor and a DL-dihydrolipoamide as acetyl acceptor (DL-dihydrolipoamide replacing the dihydrolipoyl moieties covalently bound to the lipoyl domain) in the reaction reversed from the physiological reaction (see Reaction 1) (23,24,(45)(46)(47). The acetyltransferase activity had been measured in a coupled assay with phosphotransacetylase, where the formation of a thioester bond (S-acetyldihydrolipoamide) was monitored at 240 nm (233 nm) (23,24,46), or by detection of the radioactive S-acetyldihydrolipoamide formed from [1-14 C]acetyl-CoA (45, 47).…”
Section: Functional Competence Of E2pcd Is Revealed By Pdhc Activity mentioning
confidence: 99%